Smarandache Summands

 

Edited by M. Bencze

Sacele, Romania

 

 

 

Let n>k≥1 be two integers. Then a Smarandache Summand is defined as:

 

S(n, k) = ∑ (n-ki) [for signed numbers]

0<|n-ki|≤n

i=0, 1, 2, .

 

S|n, k| = |n-ki| [for absolute value numbers]

0<|n-ki|≤n

i=0, 1, 2, .

 

which are duals and semi-duals respectively of Smarandacheials.

 

S(n, 1) and S(n, 2) with corresponding S|n, 1| and S|n, 2| are trivial.

 

a)      In the case k=3:

 

S(n, 3) = (n-3i) = n+(n-3)+(n-6)+ ; [for signed numbers].

0<|n-3i|≤n

i=0, 1, 2, .

 

S|n, 3| = |n-3i| = n+|n-3|+|n-6|+ ; [for absolute value numbers].

0<|n-3i|≤n

i=0, 1, 2, .

 

Thus S(7, 3) = 7+(7-3)+(7-6)+(7-9)+(7-12) = 7+(4)+(1)+(-2)+(-5) = 5; [for signed numbers].

Thus S|7, 3| = 7+|7-3|+|7-6|+|7-9|+|7-12| = 7+4+1+2+5 = 19; [for absolute value numbers].

 

The sequence is S(n, 3): 3, 2, 0, 5, 3, 0, 7, 4, 0, 9, 5, 0, ; [for signed numbers].

The sequence is S|n, 3|: 7, 12, 18, 19, 27, 36, 37, 48, ; [for absolute value numbers].

 

4) In the case k=4:

 

S(n, 4) = (n-4i) = n+(n-4)+(n-8) ; [for signed numbers].

0<|n-4i|≤n

i=0, 1, 2, .

 

S|n, 4| = |n-4i| = n+|n-4|+|n-8| ; [for absolute value numbers].

0<|n-4i|≤n

i=0, 1, 2, .

 

Thus S(9, 4) = 9+(9-4)+(9-8)+(9-12)+(9-16) = 9+(5)+(1)+(-3)+(-7) = 5; for signed numbers.

Thus S|9, 4| = 9+|9-4|+|9-8|+|9-12|+|9-16| = 9+5+1+3+7 = 25; [for absolute value numbers].

 

The sequence is S(n, 4) = 3, 0, 4, 0, 5, 0, 6, 0, 7, 0, 8, 0, 9, 0, 10, 0, 11, .

The sequence is S|n, 4| = 9, 16, 16, 24, 25, 36, 36, 48, 49, 64, 64, 80, 81, 100, 100, .

 

5) In the case k=5:

 

S(n, 5) = (n-5i) = n+(n-5)+(n-10) .

0<|n-5i|≤n

i=0, 1, 2, .

 

S|n, 5| = |n-5i| = n+|n-5|+|n-10| .

0<|n-5i|≤n

i=0, 1, 2, .

 

Thus S(11, 5) = 11+(11-5)+(11-10)+(11-15)+(11-20) = 11+6+1+(-4)+(-9) = 5.

Thus S|11, 5| = 11+|11-5|+|11-10|+|11-15|+|11-20| = 11+6+1+4+9 = 31.

 

The sequence is S(n, 5): 3, 6, 2, 6, 0, 5, 10, 3, 9, 0, 7, 14, 4, 12, 0, .

The sequence is S|n, 5|: 11, 12, 20, 20, 30, 31, 32, 33, 45, 60, 61, 62, 80, 80, 100, .

 

 

More general:

Let n>k≥1 be two integers and m≥0 another integer.

Then the Generalized Smarandache Summand is defined as:

 

S(n, m, k) = (n-ki) [for signed numbers].

i=0, 1, 2, , floor[(n+m)/k].

 

S|n, m, k| = |n-ki| [for absolute value numbers].

i=0, 1, 2, , floor[(n+m)/k].

 

For examples:

S(7, 9, 2) = 7+(7-2)+(7-4)+(7-6)+(7-8)+(7-10)+(7-12)+(7-14)+(7-16)

= 7+(5)+(3)+(1)+(-1)+(-3)+(-5)+(-7)+(-9) = -2.

S|7, 3, 2| = 7+|7-2|+|7-4|+|7-6|+|7-8|+|7-10| = 7+5+3+1+1+3 = 20.

 

 

References:

J. Dezert, editor, Smarandacheials, Mathematics Magazine, Aurora, Canada, No. 4/2004;

http://fs.unm.edu/Smarandacheials.htm.

F. Smarandache, Back and Forth Factorials, Arhivele Statului, Filiala Valcea, Rm. Valcea, Romania,  1972;

and Arizona State Univ., Special Collections, 1990.